2021
DOI: 10.1158/1535-7163.mct-21-0035
|View full text |Cite
|
Sign up to set email alerts
|

Belantamab Mafodotin (GSK2857916) Drives Immunogenic Cell Death and Immune-mediated Antitumor ResponsesIn Vivo

Abstract: B-cell maturation antigen (BCMA) is an attractive therapeutic target highly expressed on differentiated plasma cells in multiple myeloma (MM) and other B-cell malignancies. GSK2857916 (belantamab mafodotin, BLENREP) is a BCMA-targeting antibody-drugconjugate approved for the treatment of relapsed/refractory MM. We report that GSK2857916 induces immunogenic cell death in BCMA-expressing cancer cells and promotes dendritic cell activation in vitro and in vivo. GSK2857916 treatment enhances intra-tumor immune cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 52 publications
0
49
0
1
Order By: Relevance
“…Belantamab mafodotin (belamaf® or blenrep®) is the first in class member of the ADCs in MM that utilizes a humanized monoclonal antibody which targets B cell maturation antigen (BCMA) [ 6 8 ]. BCMA is a soluble transmembrane glycoprotein that is a member of the tumor necrosis factor superfamily (TNFRSF17) and is overexpressed on mature B cells and plasma cells [ 8 ]. The cytotoxic payload is monomethyl auristatin F (MMAF) and it is bound to the antibody via a protease resistant maleimidocaproyl linker [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Belantamab mafodotin (belamaf® or blenrep®) is the first in class member of the ADCs in MM that utilizes a humanized monoclonal antibody which targets B cell maturation antigen (BCMA) [ 6 8 ]. BCMA is a soluble transmembrane glycoprotein that is a member of the tumor necrosis factor superfamily (TNFRSF17) and is overexpressed on mature B cells and plasma cells [ 8 ]. The cytotoxic payload is monomethyl auristatin F (MMAF) and it is bound to the antibody via a protease resistant maleimidocaproyl linker [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The first tests performed in 2014 showed that belantamab-mafodotin kills the MM cells not only via ADCC but also via macrophage-mediated phagocytosis: actually, the administration of this novel molecule into the long bone of mouse models was significantly associated with increased macrophage infiltration. All death-markers released by cells targeted with belantamab promote dendritic cell activation, potentially inducing a long-lasting adaptive immune response against the tumor [ 58 ]. Therefore, belantamab-mafodotin drives immunogenic cell death, being responsible for novel modalities of MM suppression.…”
Section: Arriving To the Newest: The “Combined” Monoclonal Antibodiesmentioning
confidence: 99%
“…Recently, the FDA-approved drug belantamab mafodotin (GSK2857916), an ADC that targets B-cell maturation antigen (BCMA) in multiple myeloma cells using MMAF as a payload, induced ICD in BCMA-expressing cancer cells and promoted DC activation in vivo ( Yu et al, 2020 ). In a syngeneic mouse model, GSK2857916 was shown to induce ICD, promoting the intratumoral enrichment of TILs and T cell-dependent anti-tumor activity ( Montes de Oca et al, 2021 ). To further optimize the targeted immunomodulatory effects of ADCs, researchers have screened potential targets of ADCs that are not just limited to malignant cells.…”
Section: Attempts To Improve the Immunomodulatory Effect Of Chemother...mentioning
confidence: 99%